DEVELOPMENT OF METHODS FOR OBTAINING BAA, WHICH IMPROVES THE QUALITY OF BAKERY PRODUCTS, BASED ON THE GRAINS COLLECTED - Mirxodjayeva Dilobar Davronbekovna; Sanayev Ermat Shermatovich; Turabdjanov Sadritdin Mahamadinovich; Azamatov Umid Zokirovich (American Journals, 2024)
Grains harvested, grains containing all the original Bran and endosperm, are 100% germinated, but their nutritional values do not decrease unless they become grass. The use of germinated grain activates metabolism, resulting in the synthesis of secondary metabolites such as various enzymes, vitamins and phytochemicals, degradation to increase digestion of macronutrient compounds such as proteins and carbohydrates, and is often used as a way to improve the nutritional value of grain.
Keywords: Bread baking, multicomponent enhancer, germination, quality of grain freshness.